Menstimulasi Perkembangan Kognitif Anak Melalui Permainan Tradisional Congklak Pada Paud Kelas B (Usia 5-6 Tahun), Tahun Ajaran 2023/2024 - Hully; Nurul Iman; Reni Andriani; Baiq Sarlita Kartiani (Jurnal Pengabdian kepada Masyarakat Cahaya Mandalika (Abdimandalika), 2023)
Cognitive Ability of Group B Children through the traditional congkak game in Group B PAUD Age 5-6 Years. The aim of this service is to "Train the Cognitive Abilities of Group B Children through games for children aged 5-6 years 2023". This is based on teachers' lack of experience and skills in utilizing learning media sources, especially in stimulating children's cognitive development properly. The method used in this community service activity is participatory training and mentoring. All teachers and students at the institution become training participants in community service. Implementation of this community service activity includes providing material regarding teacher strategies in developing or modifying paper used for weaving to train children's fine motor skills. To maintain the sustainability of the results of this activity, mentoring continues to be carried out between teachers, students and the community service implementation team so that the objectives of implementing community service activities can be achieved optimally.